The politics of identity, belonging and exclusion : Chinese immigrant parents' involvement in New Zealand early childhood education : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Arts, Massey University, Albany, New Zealand - Chan, Angel (Massey University, 2014)
Parental involvement and parent-teacher partnership are key notions promoted in the New Zealand early childhood curriculum, and their value for children’s learning and development is nationally and internationally recognised. This study employed a life story methodology and a range of relevant theoretical frames, including theoretical and conceptual approaches concerning identity, social spaces, transnationalism and critical multiculturalism to explore Chinese immigrant parents’ participatory experiences in their children’s early childhood education in New Zealand and the factors that influenced their involvement. A documentary analysis identified many of the dominant discourses and practices prevalent in New Zealand early childhood education. Ten Chinese immigrants from the People’s Republic of China, recruited from three public kindergartens in Auckland, participated in two phases of individual face-to-face interviews, which focused on their involvement in the kindergartens and their perspectives of parenting, teaching and learning. The participants took pride in their Chinese identity and were determined to maintain their Chinese heritage. They had high expectations for their children’s education and were actively involved in their learning in private spaces. However, their participation in the kindergartens was passive and minimal. Utilising the technique of critical discourse analysis, an unequal positioning of discourses was revealed when narrative data was interpreted against textual findings. The participants’ stories indicated that they felt the teachers were not prepared to embrace diverse familial funds of knowledge. Their parental i aspirations and concerns were often dismissed and silenced while the dominant discourses were institutionally reinforced, thus perpetuating the participants’ essentialised beliefs regarding New Zealand and Chinese ways of teaching and learning, whilst placing cultural beliefs and practices in binary opposition. Without a sense of entitlement and belonging, the participants excluded themselves from the kindergartens. Although they reluctantly accepted the dominant discourses in public spaces, they actively employed strategies within private spaces to fulfil their parental aspirations. They fluidly utilised a range of transnational and transcultural spatial strategies to mix and match practices from both the home and host country in order to maximise the learning opportunities and achievements of their children. This thesis concludes with pedagogical recommendations informed by critical multiculturalism.
Keywords: Early childhood education; New Zealand; Parent participation; Chinese; Parent and child; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education